Evaluation of pelvic organ prolapse by standardized POP Q system for vaginal hysterectomy - Dhama, Vandana; Chaudhary, Rachna; Singh, Shakun; Singh, Manisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Uterovaginal prolapse is a common condition affecting women in reproductive and perimenopausal age groups. Evaluating pelvic organ prolapse in an objective, reproducible, easy to apply method is required for proper management. Aim of the study was preoperative and postoperative evaluation of pelvic organ prolapse by POP Q system in patients undergoing vaginal hysterectomy. Methods: In this observational study, 100 patients having pelvic organ prolapse, (average age 48±12 years), underwent elective vaginal hysterectomy at Lala Lajpat Rai Memorial Medical College Meerut during June 2015 to July 2016. POP Q was done preoperatively and after completion of surgery by the same surgeon. Results: The mean of genital hiatus preoperatively was 6.4 and post operatively it was 3.64 i.e. the genital hiatus was reduced by 2.76. The mean of total vaginal length pre-operatively was 8.07 and post operatively was 7.2. There was only 0.9 cm reduction in the vaginal length. The mean of perineal body pre-operatively was 2.64 and post operatively was 3.64. The points preoperatively were Aa 2.35, Ba 2.61, C 2.57, Ap 2.24, Bp 0.96, D-4.79 and post-operative the value of the points was -2.19, -2.04,-5.57,-2.98,-2.52 respectively and D point absent due to hysterectomy. Conclusions: The post-operative POP Q was analysed and the patients having grade 0 were 63 (optimum anatomical outcome) and patients having grade 1 were 36 (satisfactory anatomical outcome).